2010
DOI: 10.4284/sej.2010.77.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Testing Conflicting Political Economy Theories: Full‐Fledged versus Partial‐Scope Regional Trade Agreements

Abstract: Abstract:The median voter approach to trade policies within a Heckscher-Ohlin framework predicts that trade policy is pro-labor; while the lobbying model based on the argument of the free rider problem predicts that trade policy is pro-capital. We test these conflicting political economy theories using data on regional trade agreements (RTAs). Due to the violation of the conditional independence assumption of RTAs, we apply a duration analysis rather than standard binary choice analysis to the RTA panel data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The results mean that the RTA promotes international trade [14,16], and there is a possibility that the RTA conflicts with the WTO and promotes blocks of countries on the other hand. In the past, trading blocks have decreased international trade.…”
Section: Estimated Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The results mean that the RTA promotes international trade [14,16], and there is a possibility that the RTA conflicts with the WTO and promotes blocks of countries on the other hand. In the past, trading blocks have decreased international trade.…”
Section: Estimated Resultsmentioning
confidence: 95%
“…[7] found that the integration in the Euro area had a positive effect on economic growth. Other studies (e.g., [8][9][10][11][12][13][14]) examined the effect of RTA on bilateral trade. [15,16] showed that the introduction of the U.S. dollar as the domestic currency would be beneficial to APEC countries.…”
Section: Introductionmentioning
confidence: 99%
“…32 Grossman and Helpman (1995) do provide a framework for studying exclusions in FTAs, but that part of their paper has been inexplicably neglected in the subsequent literature. Empirically, we are only aware of Liu's (2009) study of how the influence of special interest groups relative to voters shapes the choice between "partial-scope" and "full-fledged" RTAs ( Figure 1 represents the latter), and of Vicard's (2009) analysis of how the history of conflicts between countries affects their choice of type of RTAs.…”
Section: Resultsmentioning
confidence: 99%
“…One reason could be that RTAs could help reduce volatility, even if they do not significantly alter growth. The costs imposed by a volatile macroeconomic environment on investment, educational attainment, income distribution and poverty are well documented, implying that reducing volatility of growth could be a valid reason for why politicians are keen to sign RTAs (for a summary, see Gavin and Hausmann, 1996;Liu, 2008).…”
Section: Introductionmentioning
confidence: 99%